ANALYSIS OF METHODS OF LEGAL PROTECTION OF CONSUMER RIGHTS IN BANKING LEGAL RELATIONS IN THE KYRGYZ REPUBLIC (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
Improving the laws governing legal relations is the main factor in the economic development of our country. This factor is responsible not only for the well-being of every citizen, but also plays a big role for the development of the economy as a whole. This article examined the improvement of laws regulating the rights of consumers in the banking market. A scientific and comparative analysis of current laws in this area was also carried out. A number of ideas were proposed that were substantiated by scientific research, in particular by the methods of legal science.
Keywords: consumer; banking services; regulations; rights; protection of rights; society; state; legal analysis